2017
DOI: 10.1186/s12920-017-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Aftermath of bustamante attack on genomic beacon service

Abstract: BackgroundWith the enormous need for federated eco-system for holding global genomic and clinical data, Global Alliance for Genomic and Health (GA4GH) has created an international website called beacon service which allows a researcher to find out whether a specific dataset can be utilized to his or her research beforehand. This simple webservice is quite useful as it allows queries like whether a certain position of a target chromosome has a specific nucleotide. However, the increased integration of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…For each methylation Beacon, we randomly sample 60 patients to construct its Beacon database. We follow the approach of previous works on Beacons testing with uniform sets of patients [36], [29], [1], [45]. This ensures the attacker can only exploit individual variances and not disease-induced systematic differences, i.e., variances that are unavoidably in the data.…”
Section: B Evaluation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each methylation Beacon, we randomly sample 60 patients to construct its Beacon database. We follow the approach of previous works on Beacons testing with uniform sets of patients [36], [29], [1], [45]. This ensures the attacker can only exploit individual variances and not disease-induced systematic differences, i.e., variances that are unavoidably in the data.…”
Section: B Evaluation Resultsmentioning
confidence: 99%
“…Despite the coarse-grained answer format, researchers have shown that the genomic Beacon is vulnerable to privacy attacks, in particular membership inference attacks [36], [29], [1], [45]. In addition, previous works have demonstrated the serious privacy risks stemming from sharing DNA methylation data [3], [8].…”
Section: A Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shringarpure and Bustamante discussed different countermeasures, such as (i) increasing the beacon size, (ii) sharing only small genomic regions, (iii) using single population beacons, (iv) not publishing the metadata of a beacon, and (v) adding control samples to the beacon dataset [13]. Lately, Aziz et al proposed two algorithms which are based on randomizing the response set of the beacons with the goal of protecting beacon members' privacy while maintaining the efficacy of the beacon servers [1]. Raisaro et al have analyzed the behavior of the beacon when applying three different countermeasures [10].…”
Section: Discussionmentioning
confidence: 99%
“…S3 was not chosen as a baseline in Track 2 because we assumed the beacon service does not keep track of the queries per individual. The performance of our baseline 35 and performance of the top two teams, the first from Vanderbilt University 36 and the second from the University of Manitoba, 37 are depicted in the Fig. 1.…”
Section: Track 1: Practical Protection Of Gds Through Beacon Servicesmentioning
confidence: 99%